Pengaruh Social Media Disorder terhadap Penerimaan Diri pada Kelompok Usia Emerging Adulthood - Trie Isabella Wulandari; Lilim Halimah (UNISBA Press, 2022)
Abstract. Emerging Adulthood is an individual with an age range of 18-25 years (6). explained that in adulthood, individuals often experience confusion, difficulties, difficulties, confusion that can inhibit self-function and lead to indications of disturbances, this is because individuals at this time are in a phase of self-exploration. The World Bank report entitled Harnessing Digital Technologies for Inclusion in Indonesia 2021 says that the age group appears to be adults with a duration of about 9.7 hours per day. One of the maladaptive uses of social media is to do a good comparison with them in accepting themselves (2). The research method used in this research is to use quantitative research methods with the number of research subjects as many as 213 respondents. The data analysis technique used in this study uses a statistical technique of simple linear regression analysis with the help of the Statistical Product and Service Solutions (SPSS) version 25.0 application. Based on the results of the calculation of the data obtained, it shows that Social Media Disorder has an influence with a significance level of 0.00<0.05 on self-acceptance in the adult age group who lives in West Java. That is, the results of this study indicate that social media disorder has a significant effect on self-acceptance in the emerging maturity age group in West Java. Abstrak. Emerging Adulthood merupakan individu dengan rentang usia 18-25 tahun (6). menjelaskan bahwa pada masa emerging adulthood individu seringkali mengalami kebingungan, kecemasan, kesulitan, kebingungan yang dapat menghambat fungsi diri dan mengarah pada indikasi terjadinya gangguan mental hal tersebut dikarenakan individu pada masa ini berada pada fase eksplorasi diri. laporan Bank Dunia berjudul Harnessing Digital Technologies for inclusion in Indonesia 2021 mengatakan bahwa kelompok usia emerging adulthood menghabiskan waktu sekitar 9,7 jam perhari. Penggunaan media sosial yang maladaptif salah satunya ialah dengan melakukan perbandingan penampilan yang berkaitan dengan ketidakpuasan mereka dalam menerima diri (2). Metode penelitian yang digunakan dalam penelitian ini adalah menggunakan metode penelitian kuantitatif dengan jumlah subjek penelitian sebanyak 213 orang responden. Teknik analisis data yang digunakan dalam penelitian ini menggunakan teknik statistik analisis regresi linear sederhana dengan bantuan aplikasi Statistical Product and Service Solutions (SPSS) versi 25.0. Berdasarkan hasil perhitunggan data yang diperoleh menunjukan bahwa Social Media Disorder memiliki pengaruh dengan tingkat signifikansi sebesar 0,00<0,05 terhadap penerimaan diri pada kelompok usia emerging adulthood yang berdomisili di Jawa Barat.Artinya, hasil penelitian ini menunjukan bahwa social media disorder berpengaruh signifikan terhadap penerimaan diri pada kelompok usia emerging adulthood di Jawa Barat.